PENGATURAN JARAK TANAM PADI (ORYZA SATIVA L.) PADA SISTEM TANAM JAJAR LEGOWO - Sakti Karokaro; Johannes E.X. Rogi; S. David Runtunuwu; Pemmy Tumewu (Universitas Sam Ratulangi, 2015)
ABSTRACT The purpose of this study was to determine the effect of plant spacing on growth and yield of paddy Legowo row planting system. The study was conducted in South Minahasa District, District Tompaso New, Village Torout for 4 months from April - August 2014 in this study used materials rice seed Bulawan, taken from the village of Torout (one's own). Research was conducted using a randomized block design (RAK) with 5 treatments spacing grown using Legowo row planting system 2: 1. Each treatment was repeated four times, namely 1) 20 x 20 cm (control), 2) 20 x 20 cm, 3) 20 x 25 cm, 4) 20 x 30 cm, 5) 20 x 35 cm. Using the method of using the F test and if there is a treatment effect followed by a test of Least Significant Difference (LSD) at 5%. Spacing of rice that gives the best results are rice treated with a spacing of 20 x 25 cm Legowo row planting system. Keywords :jajar legowo, rice